Analysis of Tax Volunteers Experiences and Challenges in Bridging Taxpayers Digital Divide During the Implementation of the Coretax Administration System - Ida Ayu Trisna Yudi Asri; Kadek Dian Jatiwardani; Desak Rurik Pradnya Paramitha Nida (Journal of Governance, Taxation and Auditing, 2026)
The digital transformation of tax administration through the implementation of the Coretax Administration System requires taxpayers to adapt to digital-based tax services. However, disparities in digital literacy remain a significant challenge that affects the effectiveness of the system implementation. This study aims to analyze the experiences, challenges, and strategies of tax volunteers in bridging the digital literacy gap among taxpayers during the implementation of Coretax. A descriptive qualitative approach was employed, with data collected through in-depth interviews, observations, and a literature review involving five tax volunteers from Universitas Warmadewa assigned to the West Denpasar Tax Office. The findings reveal that tax volunteers play a crucial role as digital facilitators by providing direct assistance, simplifying complex information, demonstrating the use of the system, and coordinating with tax officers to resolve technical issues. The main challenges identified include low levels of digital literacy among taxpayers and technical problems associated with the Coretax system. Therefore, strengthening the competencies of tax volunteers, improving taxpayers' digital literacy, and optimizing system quality are essential factors in supporting the successful digital transformation of tax administration.